Tropical seaways played a more important role than high latitude seaways in Cenozoic cooling - Z. Zhang; K. H. Nisancioglu; F. Flatøy; M. Bentsen; I. Bethke; H. Wang (Climate of the Past, 2011)
Following the Early Eocene climatic optimum (EECO, ~55–50 Ma), climate deteriorated and gradually changed the earth from a greenhouse into an icehouse, with major cooling events at the Eocene-Oligocene boundary (∼34 Ma) and the Middle Miocene (∼15 Ma). It is believed that the opening of the Drake Passage had a marked impact on the cooling at the Eocene-Oligocene boundary. Based on an Early Eocene simulation, we study the sensitivity of climate and ocean circulation to tectonic events such as the closing of the West Siberian Seaway, the deepening of the Arctic-Atlantic Seaway, the opening of the Drake Passage, and the constriction of the Tethys and Central American seaways. The opening of the Drake Passage, together with the closing of the West Siberian Seaway and the deepening of the Arctic-Atlantic Seaway, weakened the Southern Ocean Deep Water (SODW) dominated ocean circulation and led to a weak cooling at high latitudes, thus contributing to the observed Early Cenozoic cooling. However, the later constriction of the Tethys and Central American Seaways is shown to give a strong cooling at southern high latitudes. This cooling was related to the transition of ocean circulation from a SODW-dominated mode to the modern-like ocean circulation dominated by North Atlantic Deep Water (NADW).